Development of the Japanese version of the Quality of Life in Late‐stage Dementia Scale. Issue 2 (6th February 2018) - Nagata, Yuma; Tanaka, Hiroyuki; Ishimaru, Daiki; Uematsu, Masayasu; Naito, Yasuo; Nishikawa, Takashi
Abstract : Aim: Until now, there has been no instrument to measure the quality of life (QoL) of patients with severe dementia in Japan. The purpose of this study was to translate the Quality of Life in Late‐stage Dementia Scale and to evaluate the reliability and validity of the Japanese version (QUALID‐J). Methods: We translated the Quality of Life in Late‐stage Dementia into Japanese with permission from the original authors. We assessed a total of 70 dementia patients (14 men, 56 women; mean age: 87.4 ± 7.9 years) with the QUALID‐J. Results: The test–retest and inter‐rater reliability of the QUALID‐J was significant. With regard to the criterion‐related validity, the correlation coefficient for the total score between the QUALID‐J and Quality of Life for Alzheimer's Disease was −0.287 ( P  < 0.05). With regard to the construct validity, the QUALID‐J total score was significantly correlated with the Mini‐Mental State Examination ( ρ  = −0.346, P  < 0.01), the Cognitive Test for Severe Dementia ( ρ  = −0.323, P  < 0.01), the Neuropsychiatry Inventory‐Nursing Home version ( ρ  = 0.386, P  < 0.01), the Cornell Scale for Depression in Dementia ( ρ  = 0.262, P  < 0.05), the Physical Self‐Maintenance Scale ( ρ  = −0.283, P  < 0.05), and the Pain Assessment in Advanced Dementia ( ρ  = 0.530, P  < 0.01). Conclusion: The results of this study showed that the QUALID‐J is a reliable and valid quality of life scale for severe dementia. This scale finally enables an adequate assessment of the quality of life of patients with severe dementia in Japan, which has not been possible until now.